Research on the Image Background Base Algorithm Based on the Factor Space Theory - Pengxue Zhang; Xiaoyu Bi (Computer Sciences & Mathematics Forum)
Image vision has wide application prospects in the field of intelligent manufacturing, and studying an effective background base extraction algorithm has become an urgent need for factor space applications in the fields of big data and image vision. Based on this, an image background base extraction algorithm for identifying image information is proposed. The algorithm analyzes the characteristics of the base points in the image and converts the brightness changes observed by the human eye into the data language form that the machine can read. Numerical experiments show the effectiveness and robustness of the proposed algorithm.